Effects of an Innovative Training Program for New Graduate Registered Nurses: A Comparison Study. (February 2021) - Xu, Fengqin; Ma, Liang; Wang, Yinhe; Yu, Jiang; Li, Dandan; Zhou, Guohui; Xu, Yuzi; Zhang, Hailin; Cao, Yang
New graduate registered nurses (NGRNs) face a great challenge during the transition from school to clinical practice. We conducted a quasi-randomized controlled study to evaluate the effects of a new training mode for newly recruited NGRNs in a Chinese teaching hospital. A total of 150 NGRNs were recruited from a teaching hospital and assigned into two groups. The conventional training and a new training program were taken for the control group and the research group, respectively. At the end of the training, the two groups were evaluated and compared for theoretical knowledge and operation skills using a mutual-evaluation examination and the Chinese Registered Nurse Core Competency Scale. The scores of theoretical knowledge (88.4 vs. 81.7, p < .001) and operation skills (94.8 vs. 90.3, p < .001), and the total core competencies score (156.2 vs. 148.8, p < .05) in the research group were statistically significantly higher than those in the control group. Compared with the control group, the research group also had statistically significantly higher scores in education and consultation (2.47 vs. 2.40), clinical nursing (2.87 vs. 2.62), interpersonal relationship (2.56 vs. 2.43), and critical thinking and scientific research (2.78 vs. 2.61). The innovative pre-job training program for NGRNs conducted in Chinese clinical nursing skill training bases might significantly improve the training effects and is worthy of broader implementation.